Răspuns:
Explicație pas cu pas:
1.a) 2x+1 = -5 <=>
2x = -1-5 =>
2x = -6 =>
x = -6:2 =>
x = 3
b) 0,5·x-1,3 = 2,7 =>
0,5·x = 2,7+1,3 =>
0,5·x = 4 => x = 4:0,5 =>
x = 8
c) √3x = 2√6 => x = 2√6 : √3 => x = 2√2
2. 2(x+1)-3(2-x) = x+3(2x+1) <=>
2x+2-6+3x = x +6x+3 <=>
5x -4 = 7x + 3 =>
7x-5x = -4-3 =>
2x = -7 =>
x = -7/2
3. 3+2x²-(x-2²) = -3x-7 <=>
3+2·(-1)² - (-1-2²) = -3(-1) - 7 <=>
3+2·1-(-5) = 3-7 <=>
3+2+5 = -4 <=>
10 = -4 incorect
3'. 3+2x²-(x-2)² = -3x-7 <=>
3+2(-1)²-(-1-2)² = -3(-1)-7 <=>
3+2-9 = 3-7 <=>
-4 = -4 ; corect